1992
DOI: 10.1039/jm9920200231
|View full text |Cite
|
Sign up to set email alerts
|

Study of the system Ca3(AsO4)2–CaSO4by solid-state reaction

Abstract: Study of the system Ca,(AsO,),-CaSO, has led to the preparation of a series of solid solutions whose general formula is [(Ca,, --x 0,,,)(As0,),,~,,(S0,),, O,] with O < x < 1. These solid solutions are isostructural with tricalcium orthoarsenate Ca,(AsO,),. The limit of solubility of sulfate ions in tricalcium orthoarsenate corresponds to the ionic ratio R=SOZ-/AsOZ-=0.167 (corresponding to x = 1 in the general formula). The limit compound, calcium arsenosulfate Ca,,(AsO,),,(SO,),, is characterized by its infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In recent years, considerable progress has been made in the development of fixed-grid enthalpy-based macroscopic models, [1] in order to simulate transport phenomena during alloy solidification processes. In such models, enthalpy is related to the liquid fraction of a control volume in the phase changing domain, in an implicit fashion, without the requirement of any explicit imposition of interfacial boundary conditions, which is in sharp contrast with the so-called moving grid front-tracking algorithms.…”
Section: Suvankar Ganguly and Suman Chakrabortymentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, considerable progress has been made in the development of fixed-grid enthalpy-based macroscopic models, [1] in order to simulate transport phenomena during alloy solidification processes. In such models, enthalpy is related to the liquid fraction of a control volume in the phase changing domain, in an implicit fashion, without the requirement of any explicit imposition of interfacial boundary conditions, which is in sharp contrast with the so-called moving grid front-tracking algorithms.…”
Section: Suvankar Ganguly and Suman Chakrabortymentioning
confidence: 99%
“…Recent experimental studies [1,2] have demonstrated that solid-solid reactions exist between CaSO 4 and Ca 3 (AsO 4 ) 2 at elevated temperatures. These two compounds appear to form an intermediate phase with the following composition: Ca 10 (AsO 4 ) 6 (SO 4 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The binary solid solution Ca 3 (AsO 4 ) 2 -CaSO 4 was studied by Marraha et al [24] In a previous publication, [5] we proposed a model for this binary solid solution (Figure 2). The crystal structure of Ca 3 (AsO 4 ) 2 has been studied in detail.…”
Section: F Thermodynamic Model Of the Ca 3 (Aso 4 ) 2 Solid Solutionmentioning
confidence: 99%
“…Consider When CaSO 4 dissolves in Ca 3 (AsO 4 ) 2 , it was demonstrated by Marraha et al [24] that the ion substitutes for an ion, which is of similar size. Furthermore, substitution for an {AsO 4 } on the A chain, with a vacancy occupying the [Ca,Va] site, should be a preferred configuration because this will result in local charge neutrality.…”
Section: F Thermodynamic Model Of the Ca 3 (Aso 4 ) 2 Solid Solutionmentioning
confidence: 99%